Etika Regulasi dan Kebijakan Media Digital: Meningkatkan Kesadaran Publik di Era Informasi - Tumanggor, Timur; Sazali, Hasan (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
This study aims to critically analyze the importance of ethics in the regulation and policy of digital media to enhance public awareness in the information age. The research employs a literature review method by analyzing policy documents, legislation, and previous studies related to the implementation of the Electronic Information and Transaction Law (UU ITE) in Indonesia. The findings reveal a gap between legal norms and digital practices in society, as indicated by multiple interpretations of legal articles, low digital literacy, unequal access to technology, and weak protection of digital rights, including privacy and data control. The analysis highlights that ethical, user-centric, and inclusive policies—supported by digital literacy and multi-stakeholder participation—can improve digital rights protection and public awareness. This study recommends the reformulation of digital media policies to be more ethical, inclusive, and responsive as an effort to build a fair, democratic, and civilized digital ecosystem.